A prediction model for the oceanauts’ cognitive performance based on the mental workload of typical tasks - Mengya Zhu; Jingluan Wang; Xian Zhang; Dengkai Chen (BMC Psychology)
Abstract High-level cognitive abilities are essential for the oceanauts to successfully complete the tasks, such as assessing cruising positions, operating interface commands, and responding to voice instructions. However, it is still unknown which variables impact oceanauts’ cognitive performance and how, and how best to create and implement analytic approaches to predict oceanaut’s personalized cognitive performance. As a result, we attempted to conduct cognitive tests trials on four typical activities among oceanauts. Oceanaut cognition characteristics were collected in order to create a quantitative model of cognitive performance. We utilised Radial Basis Functions to predict the oceanauts’ cognitive performance and investigated the impact of mental workload, personal characteristics, and comfort on their cognitive performance. The findings indicated that establishing an appropriate level of mental workload for the visual, auditory, cognitive, and psychomotor channels can enhance the oceanaut’s cognitive performance of individuals engaged in ocean exploration. It is worth noting that the optimal values for mental workload vary across these channels. Furthermore, the presence of suitable comfort, appropriate age, and a relatively higher level of educational background contribute to the enhancement of cognitive performance among oceanauts.